Trophospheric carbon monoxide trends over malaysia using satellite-sensed data for a period of 2000-2018 / Zildawarni Irwan, Abdul Rahman Mat Amin and Noor Erni Fazlina Mohd. Akhir - Irwan, Zildawarni; Mat Amin, Abdul Rahman; Mohd. Akhir, Noor Erni Fazlina (Universiti Teknologi MARA Cawangan Pahang, 2020)
Tropospheric carbon monoxide (CO) is one of the most significant air pollutant gas that can affect human health, as stated by United States Environmental Protection Agency (USEPA). This study aims to evaluate the trend of CO gas using 18 years of data (April 2000 - December 2018) measured by Measurements of Pollution in the Troposphere (MOPITT) over Malaysia. The results show significant decrease in concentration of CO with mean of monthly carbon monoxide of 113.25 ppbv for the entire period. The seasonal cycle of CO showed maximum levels in December-January, but minimum levels in June-August. The highest values of CO were in west region of Peninsular Malaysia throughout the year. The CO gas was highly concentrated over the west region of Peninsular Malaysia resulted from human activity and abundance sources of CO at this area due to its larger number of human populations, various industrial activities, crowded city with extremely higher traffic.